World - Climate Services Operational Pathways : Pathways for Transforming Weather, Water, and Climate Services in Mozambique - World Bank (Washington, DC, 2022)
This study was commissioned by climate investment funds (CIF’s) E and L initiative to distill lessons from CIF’s pilot program on climate resilience (PPCR) support in identifying, designing, and implementing hydrometeorological and climate services investments. It seeks to generate learning and strategic insight into the different operational pathways that can be taken by national hydrological and meteorological services to develop, deliver, and strengthen hydrometeorological and climate services. The outputs from the study comprise of one synthesis report and three country studies for Jamaica, Mozambique, and Nepal. These three countries have been selected for the study due to their different institutional frameworks, hydrometeorological systems, and socio-economic context. They provide diverse in-depth insights in hydrometeorological and climate service development, delivery and use. In this respect, the PPCR-supported Climate Resilience: Transforming Hydrometeorological Services Project was selected as a case study project for Mozambique. It elucidates lessons learned on the process for modernizing hydrometeorological systems and delivering climate services to users. Furthermore, it offers insight into challenges and opportunities for climate services development, delivery, and use in Southern African developing countries. Qualitative methods, including structured interviews and literature review, were used to identify promising pathways to continue to transform weather, water, and climate services in the three case study countries. In Mozambique, the analysis of the data collected revealed six themes regarding critical pathways to transform weather, water, and climate services in the country. These are: harmonizing and integrating data resources; improving hydrometeorological and climate service design and delivery; fostering hydrometeorological and climate services impact through user feedback; building appropriate human capacity; strengthening national coordination; and promoting regional collaboration. The report summarizes key findings.